Analisis Kinerja Pengelolaan Piutang Negara Tak Tertagih pada Kantor Pelayanan Kekayaan Negara dan Lelang Surakarta - Vika Nur Hanifah; Andi Asrihapsari (Jurnal Akuntansi dan Pajak, 2024)
The Surakarta State Wealth and Auction Service Office (KPKNL) is a vertical agency of the Directorate General of State Wealth (DJKN) which is under and directly responsible to the head of the regional office. The purpose of this study is to determine the management process, performance, as well as constraints and efforts in managing bad state receivables at the Surakarta KPKNL. The method used in this study is a combined method, namely with qualitative descriptive analysis and quantitative descriptive analysis. The data collection technique is carried out by field observation, interviews, related documents, literature studies and data obtained in the form of primary data and secondary data. The results of this study explain that the procedure for managing state receivables is in accordance with applicable regulations. The performance of state management at the Surakarta KPKNL is considered very effective because it shows a value above 100%. There are obstacles faced when managing bad state receivables and efforts made by the KPKNL Surakarta. One of the suggestions from the author in reducing the amount of bad debts is to store files properly and make data backups, so as to expedite the process of managing bad state receivables.